2023
DOI: 10.1002/epi4.12744
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of tau phosphorylation and β‐amyloid pathology in human drug‐resistant epilepsy

Abstract: Objective Epilepsy can be comorbid with cognitive impairments. Recent evidence suggests the possibility that cognitive decline in epilepsy may be associated with mechanisms typical of Alzheimer's disease (AD). Neuropathological hallmarks of AD have been found in brain biopsies surgically resected from patients with drug‐resistant epilepsies. These include hyperphosphorylation of the tau protein (p‐tau) that aggregates into neuropil threads (NT) or neurofibrillary tangles (NFT), as well as the presence of β‐amy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 58 publications
1
1
0
Order By: Relevance
“…Aβ protein levels and their relationship with cognitive function have been investigated in patients with refractory epilepsy by analyzing cortical biopsies from the temporal lobes. The results revealed a strong compelling of Aβ deposits in the biopsied tissues, supporting the existence of Aβ deposits in patients with refractory epilepsy ( 39 ). In patients with refractory seizures, increased Aβ precursor protein was detected in temporal lobe or hippocampal sections ( 41 ).…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…Aβ protein levels and their relationship with cognitive function have been investigated in patients with refractory epilepsy by analyzing cortical biopsies from the temporal lobes. The results revealed a strong compelling of Aβ deposits in the biopsied tissues, supporting the existence of Aβ deposits in patients with refractory epilepsy ( 39 ). In patients with refractory seizures, increased Aβ precursor protein was detected in temporal lobe or hippocampal sections ( 41 ).…”
Section: Discussionsupporting
confidence: 70%
“…Canine refractory epilepsy have a higher risk of developing CDS at a younger age than normal dogs ( 12 ). Multiple studies in animals and humans have revealed an association between Aβ and epilepsy ( 37 39 ). In our study, we first demonstrated significantly higher plasma Aβ levels in dogs with refractory epilepsy.…”
Section: Discussionmentioning
confidence: 99%